Voices from Afar: Cross-national study of parental perspectives towards implementation of a smart learning environment in schools in the United Arab Emirates - Maria Efstratopoulou; Maxwell Peprah Opoku; Christina Davison; Abdulrafi Jaffarul; Aalya Mesmar (International Journal of Educational Research Open, 2024)
A smart learning environment (SLE), which is the infusion of advanced technology and appropriate pedagogy, has been embraced by many countries as a useful step towards educational transformation. Consequently, in the United Arab Emirates (UAE), the SMART School Transformation Framework was designed and implemented to enhance students’ learning. However, studies on parental perception regarding the successful implementation of SLEs do not exist in the UAE and similar non-Western contexts. This cross-national study attempted to assess parents’ attitudes towards implementing smart learning in schools in the UAE. Parental attitude towards the smart learning scale was used for data collection from 2287 participants throughout the seven Emirates in the UAE. Exploratory factor analysis was used to explore the underlying factor structure of the study instrument. Subsequently, hierarchical regression, t-test and analysis of variances were calculated to develop an in-depth understanding of parental attitudes towards SLEs. Though participants were ambivalent in relation to attitudes towards smart learning, there were differences between them in terms of place of residence, gender and age. The need for policy makers to expedite public education on smart learning among parents, as well as other study implications, are discussed.